2016
DOI: 10.15414/raae.2016.19.01.50-55
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of informal credit delinquency among food crop farmers in rural niger delta of Nigeria

Abstract: The study examined the determinants of informal credit delinquencies among food crop farmers in rural Niger Delta of Nigeria using Akwa Ibom State as a case study. A multi-stage random sampling technique was adopted to select 96 beneficiaries and structured questionnaires as well as personal interview were used to collect data. Probit and logit models were used to analyse the factors influencing credit delinquency among food crop farmers in the state. Result of the descriptive analysis of the socioeconomic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
4
3
0
Order By: Relevance
“…Farmers with high incomes are also more likely to receive credit facilities from lenders since they have a better likelihood of repaying the loan. This result is in agreement with Nto (2006), Nwaru et al (2008), andEssien (2009) who reported a positive and significant relationship between credit demand and farm income. The coefficient of the age of farmers was positive and statistically significant.…”
Section: The Determinants Of Microcredit Demand Among Fish Farmerssupporting
confidence: 91%
See 3 more Smart Citations
“…Farmers with high incomes are also more likely to receive credit facilities from lenders since they have a better likelihood of repaying the loan. This result is in agreement with Nto (2006), Nwaru et al (2008), andEssien (2009) who reported a positive and significant relationship between credit demand and farm income. The coefficient of the age of farmers was positive and statistically significant.…”
Section: The Determinants Of Microcredit Demand Among Fish Farmerssupporting
confidence: 91%
“…The negative effect of interest rate indicates that a credit scheme with a higher interest rate lowers the probability of farmers' demand for microcredit and vice versa. This is in agreement with the finding of Nwaru (2004), Essien (2009) and Nwaru et al (2011), Ibrahim andAliero (2012), Ololade and Olagunju (2013), Assogba et al (2017), and Mwonge and Naho (2022). Also, from the law of demand, the higher the price of a loan charged (that is, high-interest rate), the lower the credit demand.…”
Section: The Determinants Of Microcredit Demand Among Fish Farmerssupporting
confidence: 90%
See 2 more Smart Citations
“…Recommendations such as timely disbursement of loan by banks, less burdensome administrative procedures in loan acquisition as well as development and implementation of cassava friendly loan packages were made among others. Also, Essien et al (2016) farmers in rural Niger Delta of Nigeria using Akwa Ibom State as a case study. Empirical result from the probit and logit models were similar and showed that borrower's non-farm income, credit amount received, household size, net farm profit and farm size are determinants of credit delinquencies among food crop farmers in Akwa Ibom state.…”
Section: Literature Reviewmentioning
confidence: 99%